2019
DOI: 10.3389/feart.2019.00145
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Correction of Satellite Ocean-Color Imagery During the PACE Era

Abstract: The Plankton, Aerosol, Cloud, ocean Ecosystem (PACE) mission will carry into space the Ocean Color Instrument (OCI), a spectrometer measuring at 5 nm spectral resolution in the ultraviolet (UV) to near infrared (NIR) with additional spectral bands in the shortwave infrared (SWIR), and two multi-angle polarimeters that will overlap the OCI spectral range and spatial coverage, i. e., the Spectrometer for Planetary Exploration (SPEXone) and the Hyper-Angular Rainbow Polarimeter (HARP2). These instruments, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 198 publications
(303 reference statements)
1
83
0
Order By: Relevance
“…Rather than define such constraints explicitly using ad hoc heuristics, OE captures them automatically in the statistical properties of the combined model. OE is also distinct from other simultaneous open water retrieval methods (Wang et al, 2010) which apply mainly to multi-band data or limited water properties (Frouin et al, 2019), often disregard uncertainties, and do not generally work over land.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than define such constraints explicitly using ad hoc heuristics, OE captures them automatically in the statistical properties of the combined model. OE is also distinct from other simultaneous open water retrieval methods (Wang et al, 2010) which apply mainly to multi-band data or limited water properties (Frouin et al, 2019), often disregard uncertainties, and do not generally work over land.…”
Section: Introductionmentioning
confidence: 99%
“…VSWIR spectra are sensitive to atmospheric effects ranging from extreme Rayleigh and Aerosol scattering in the ultraviolet, through pervasive water vapor effects throughout the near infrared and into deep water absorptions at 1480 and 1880 nm. Reviews are found in Thompson et al, 2018c for land andFrouin et al (2019) for open ocean. Most approaches are variations of multi-band sequential algorithms (Guanter et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We did not deliberate on the aerosol/land retrievals, but we did consider the possibilities of aerosol/ocean retrievals. These possibilities are discussed more fully in other papers appearing in this special issue (Chowdhary et al, 2019;Frouin et al, 2019;Remer et al, 2019).…”
Section: Discussion and The Path Forwardmentioning
confidence: 99%
“…The model parameters, i.e., [Chla] and bbs in MM01, and [Chla], fa, and fb in PR05, are obtained from the prescribed R rs at a set of wavelengths in the 400-900 nm spectral range using, as in POLYMER, the Nelder-Mead optimization scheme [24]. A simplex method is used to minimize the cost function f, which is defined as: f = (πŘ rs (λ i ) − πR rs (λ i )) 2 /norm, norm = 0.005 if πR rs (λ i ) < 0.005, otherwise norm = πŘ rs (λ i ), (1) whereŘ rs (λ i ) is the modeled remote sensing reflectance at wavelength λ i , and R rs (λ i ) is the Hydrolight simulated or field measured remote sensing reflectance at wavelength λ i . For the MM01 model, the first iteration simplex is defined by initial values log 10 ([Chla]) = −1 and bbs = 0, and initial steps 0.05 and 0.0005 m −1 .…”
Section: Inversion Schemementioning
confidence: 99%